Managing expectations, rights, and duties in large-scale genomics initiatives: a European comparison - Horn, RJ; Merchant, J (Springer, 2022)
This article reports on the findings of an international workshop organised by the UK-France Genomics and Ethics Network (UK-FR GENE) in 2021. They focus specifically on how collection, storage and sharing of genomic data may pose challenges to established principles and values such as trust, confidentiality, and privacy in countries that have implemented, or are about to implement, large-scale national genomic initiatives. These challenges impact the relationships between patients/citizens and medicine/science, and on each party’s rights and duties towards each other. Our geographic scope of comparative analysis includes initiatives underway in England (Genomics England), France (Plan France Médecine Génomique) and Germany (German Human Genome-Phenome Archive). We discuss existing as well as future challenges raised by large-scale health data collection and management in each country. We conclude that the prospects of improving individualised patient healthcare as well as contributing to the scientific and research prosperity of any given nation engaged in health data collection, storage and processing are undeniable. However, we also attempt to demonstrate that biomedical data requires careful management, and transparent and accountable governance structures that are clearly communicated to patients/participants and citizens. Furthermore, when third parties partake as stakeholders, transparent consent protocols relative to data access and use come centre stage, and patient benefits must clearly outweigh commercial interests. Finally, any cross-border data transfer needs to be carefully managed to address incoherencies between regional, national, and supranational regulations and recommendations.